Volleyball players training intensity monitoring through the use of spectral analysis of heart rate variability during a training microcycle - Hap, P.; Stejskal, P.; Jakubec, A. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2011)
Volleyball players in different specializations are required to meet specific demands in terms of movement behaviour and skills performance. These specific demands need to be individualized according to the training ability level (adaptability to sports training) of particular players, which is mainly dependent on the activity of the autonomic nervous system (ANS). Spectral analysis of heart rate variability (SA HRV) gives us information on cardiac activity regulation, where the activity of ANS participates in a significant way. Longitudinal assessment of SA HRV within a certain part of a training period can help us to observe the dynamics of the ANS activity and adaptability (training ability) changes of an observed player to training. OBJECTIVE: The goal of the work was to verify the possibility of volleyball players' training load optimalization during a one week training microcycle based on the longitudinal observation of dynamics of SA HRV complex indices. METHODS: The SA HRV method was used for the evaluation of autonomic cardiac regulation. The study group consisted of eight volleyball players who took part in 28 training sessions focused on conditioning and volleyball skills development. During the microcycle, there were 7 HRV examinations. RESULTS: The results demonstrated that notable and considerably varied changes in the activity of ANS in players were assessed owing to both training and extra-training stimuli. The results in two players show a high activity of ANS which enables them to increase their training intensity. Four players achieved average values of their ANS activity, which reflects a corresponding training load. In the last two players we found a very low level of their ANS activity and it refers to their reduced adaptability to the training load, which was too high for them. CONCLUSIONS: The presented results support the necessity of the individualization of, at least a part of, team training. Such an optimalization and increase of training process efficiency should lead to a sports performance improvement, also in team sports games.